The association of long-term alcohol biomarkers with risk for alcohol-related injury: Implications for screening. (4th March 2017) - Fendrich, Michael; Berger, Lisa; Fuhrmann, Daniel
Abstract: Alcohol misuse is a leading risk factor for serious injury and death. For those experiencing trauma in emergency care settings, recent alcohol misuse history is typically assessed via self-report measures. Since underreporting may be a problem in these settings, objective indicators like long-term biomarkers may be useful for identifying hazardous drinkers who may need intervention. Recognizing this, we investigated (1) whether hazardous drinking was linked to reports of alcohol-related injury in a probability sample of over 600 college students from a large, Midwestern, urban university; (2) whether elevated long-term biomarkers showed similar associations in the same sample. Associations derived from responses to the Alcohol Use Disorder Identification Test-C (AUDIT-C) as well as from hair and fingernails tested for ethyl glucuronide, a direct alcohol biomarker, suggested that hazardous drinking is significantly associated with elevated risk for alcohol-related injury. Implications for screening and intervention in health care settings are discussed.